Complete Genome Sequences of Two Bioluminescent Vibrio campbellii Strains Isolated from Biofouling Communities in the Bay of Bengal - Colston, Sophie M. (Genome Announc, 2018)
Vibrio campbellii is a pathogen of aquatic animals and has been proposed as a bacterial partner in the formation of bioluminescent milky seas. We present here the complete genome sequences assembled from Illumina and Oxford Nanopore data for two bioluminescent Vibrio campbellii strains (BoB-53 and BoB-90) isolated from biofouled moorings in the Bay of Bengal.